The Effectiveness of Guided Inquiry Learning Model on Students' Critical Thinking Ability in Simulation and Digital Communication Subjects - Septiana, Rahma; Efendi, Agus; Aristyagama, Yusfia Hafid (Universitas Sebelas Maret, 2022)
This study aims to find out the difference in students' critical thinking ability between the use of the Guided Inquiry learning model and with expository learning model and to know the effectiveness of the Guided Inquiry learning model on students' critical thinking ability in digital Simulation and Communication subjects. The subject used in this study was a Grade X student of Software Engineering SMK 2 Surakarta. The method used is a quantitative approach with a quasi-experiment that uses a nonequivalent control group design, pretest-posttest. This study used two groups: the control group with the expository learning model and the experimental group with the Guided Inquiry learning model. Sampling techniques in this study with simple random sampling. Data collection using observations and test instruments. Data analysis on hypothesis test using Independent sample T-test with an error level of 0.05. Hypothetical testing showed significant differences in post-tests between the two groups with sig values. (2-tailed) by 0.012 <0.05.